2019
DOI: 10.3390/nano9091302
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Effects of Diesel Exhaust and Metal Oxide Nanoparticles in Human Lung A549 Cells

Abstract: Airborne ultrafine particles (UFP) mainly derive from combustion sources (e.g., diesel exhaust particles—DEP), abrasion sources (non-exhaust particles) or from the unintentional release of engineered nanoparticles (e.g., metal oxide nanoparticles—NPs), determining human exposure to UFP mixtures. The aim of the present study was to analyse the combined in vitro effects of DEP and metal oxide NPs (ZnO, CuO) on human lung A549 cells. The mixtures and the relative single NPs (DEP, ZnO, CuO) were characterized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Zerboni and colleagues reported a significant concentration-dependent decrease in the number of viable A549 cells after 24 h and 48 h exposed to CuO NPs at concentrations of 15, 20, and 25 µg/mL. In contrast, ZnO NPs were not able to induce such cytotoxic effects at concentrations less than 25 µg/mL [ 17 ]. Li et al showed that low concentrations of iron oxide-based magnetic NPs markedly diminished the cell viability of A549 cells and exerted noticeable synergistic effects against malignant cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zerboni and colleagues reported a significant concentration-dependent decrease in the number of viable A549 cells after 24 h and 48 h exposed to CuO NPs at concentrations of 15, 20, and 25 µg/mL. In contrast, ZnO NPs were not able to induce such cytotoxic effects at concentrations less than 25 µg/mL [ 17 ]. Li et al showed that low concentrations of iron oxide-based magnetic NPs markedly diminished the cell viability of A549 cells and exerted noticeable synergistic effects against malignant cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that an atmosphere with a high PM2.5 and PM10 content favours the transmission of the virus by transporting it on dust particles over long distances. PM2.5 and PM10 particles also induce inflammation in the lungs, which may increase the risk of infection and exacerbate the course of COVID-19 [47][48][49][50][51]. The rapid development of the pandemic in Italian Lombardy may also have depended on air pollution in Italian cities in the region [21].…”
Section: The Hypothesis Of Additional Lung Damage and The Impact Of An Industrially Altered Environmentmentioning
confidence: 99%
“…Commercial CuO (<50 nm, CAS 1317-38-0), ZnO (<50 nm, CAS 1314-13-2), NPs, and diesel exhaust particles (DEPs; NIST SRM ® 2975) were purchased from Sigma-Aldrich (Milan, Italy). Particle suspensions and mixtures were prepared as previously described [8] and characterized (Tables S1 and S2 and Figure S1). The mixtures were freshly prepared before use.…”
Section: Preparation Of Particle Suspensions and Mixturesmentioning
confidence: 99%
“…Human alveolar epithelial cells, A549 (ATCC ® CCL-185, American Type Culture Collection, Manassas, VA, USA), were grown and maintained as previously reported [8]. For the experiments, the cells were seeded at a concentration of 1.6 × 10 4 cells/cm 2 on 6-well plates (Corning ® , Pero (MI), Italy) and grown for 24 h. At the optimal confluence (80-90%), the culture medium was replaced with fresh OptiMEM supplemented with 1% foetal bovine serum (FBS) (Gibco, Life Technologies, Monza, Italy), and the cells were treated by directly adding the different particle suspensions (ZnO, ZnO + DEP, CuO, CuO + DEP, or DEP) into the medium.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation